The Influence of Digital Advertising and Word of Mouth on Tourist Visit Interest in Kupang Kelapa Lima Beach - Ufi, Finy; Kefi, Darwin; Sayd, Imelda (Journal of Practical Management Studies, 2023)
This research is entitled "The Effect of Digital Advertising and Word of Mouth on Tourist Visit Interest at Kelapa Lima Beach Kupang". This study aims to determine whether digital advertising and word of mouth promoted by the Kupang City Tourism Office affect the interest of tourist visits to Kupang Kelapa Lima Beach. This research was conducted at Kelapa Lima Beach Kupang. The population in this study was visitors to Kelapa Lima Beach during the data collection period. The sample in this study was taken as many as 50 respondents. The sampling technique used in this study is axial sampling. Data collection techniques using Observation, Interviews, Questionnaires and documentation. The population in this study was visitors to Kupang Lima Coconut Beach. The data analysis technique uses multiple linear regression analysis techniques. The results of this study show that Digital Advertising Variables and Word of Mouth simultaneously have a positive and significant effect on Kujungan Interest in Kelapa Lima Beach Kupang.